Percutaneous Radiofrequency Ablation Is an Effective Method for Local Control of Liver Metastases From Lung Cancer - Zhang, Zhong-Yi; Jiang, An-Na; Yang, Wei; Yan, Kun; Wu, Wei; Wang, Song; Jiang, Bin-Bin; Sun, Li-Qi; Zhao, Kun; Chen, Min-Hua (Frontiers in Oncology, 2022)
Objective To investigate the clinical value of percutaneous radiofrequency ablation (RFA) for liver metastasis from lung cancer (LCLM). Materials and Methods We retrospectively enrolled 58 patients who underwent RFA for LCLM between January 2014 and December 2019. Primary lung cancer histology included 38 adenocarcinomas, 15 squamous carcinomas, and 5 small cell carcinomas. For 83 metastatic lesions (mean tumor diameter 3.3 ± 1.1 cm, range 0.9–5.0 cm), 65 RFA sessions were performed. Before RFA, 17 and 41 patients presented no and stable extrahepatic metastasis, respectively, whereas 18 and 40 patients had synchronous and metachronous liver metastasis, respectively. Survival was analyzed using the Kaplan-Meier method. Cox proportional hazards model was used for multivariable analysis. Results The technical success rate was 96.3% (80/83 lesions). Local tumor progression was observed in 8 (9.8%, 8/82) lesions of 57 (14.0%, 8/57) patients at 4–12 months after RFA. New liver metastases occurred in 27 (46.6%) patients. The overall survival (OS) rates at 1, 2, 3, and 5 years after RFA were 55.2%, 26.0%, 22.0%, and 14.4%, respectively. The median OS after RFA and after liver metastasis were 14.0 ± 1.6 and 20.0 ± 1.5 months, respectively. Based on the univariable analysis, tumor size (p=0.017), histological type (p=0.015), and timing of liver metastasis (p=0.046) were related to OS. In further multivariable analyses, squamous carcinoma (hazard ratio= 2.269, 95% confidence interval: 1.186-4.339, p=0.013) was an independent unfavorable prognostic factor for OS. Based on the univariable analysis, histological type (p=0.010) was identified as parameters significantly related to local tumor progression (LTP)-free survival. Further multivariable analyses revealed that squamous carcinoma (hazard ratio=2.394, 95% confidence interval: 1.260–4.550, p=0.008) was an independent unfavorable prognostic factor for LTP-free survival. Conclusion RFA is a safe therapeutic option for LCLM with acceptable local tumor control, especially in patients with a tumor size ≤3 cm, adenocarcinoma/small cell carcinoma, and metachronous liver metastases.